Genoese-Tatar Treaties of 1380 and 1381 in Their Historical Context. - Talakh V.N. (Золотоордынское обозрение)
Research objective: An analysis of the provisions and circumstances of the conclusion of the Genoese-Tatar treaties of November 1380 and February 1381. Research materials: Political, legal, and economic clauses of the agreements of 1380–1381, the available information on the persons who participated in their signing, the circumstances of their conclusion. Results and novelty of the research: Although the content of both documents is identical, and they differ only in the groups of people who signed them on the Horde’s side, the author argues here that these are two independent acts. According to the author, both agreements were concluded on behalf of and in the interests of Toqtamïsh Khan. Based on numismatic data, the dating of the yarliq to Bek Haji, and records in the book of Caffa’s Massaria, the author is inclined to an early dating of the establishment of Toqtamïsh Khan’ power in Crimea, namely, before March 1380. The author is of the opinion that the existence of two agreements was in connection with a change of administration in Solkhat (although the details of this are unclear). He also considers highly plausible N. Murzakevich’s assumption that the cession to the Genoese of Soldaia district and Crimean Gothia, stipulated by treaties, was a reward for the murder of Mamai which occurred perhaps between 28 November 1380 and 23 January 1381.